An alternative management procedure after inadvertent dural puncture - Kemal Tolga Saracoglu (Journal of Research in Medical Sciences, 2011)
Background: Accidental dural puncture during epidural blockade is a rare complication. Since postdural puncture headache (PDPH) is the most frequent complication, a wisely management method will also reduce the incidence of PDPH. Methods: Five patients who had inadvertent dural puncture during the epidural procedure before hip or knee arthroplasty were included in this study. After dural puncture we drew back the epidural needle and placed an epidural catheter into the epidural space. Results: Epidural anesthesia and postoperative epidural analgesia have been provided successfully in all cases. 20% showed PDPH. Conclusions: These results demonstrate the effectiveness of management skills after inadvertent dural punctures.